Allocating Effort and Talent in Professional Labor Markets - Gadi Barlevy; Derek Neal (Institute for the Study of Labor (IZA), 2016)
In many professional service firms, new associates work long hours while competing in up-or-out promotion contests. Our model explores why these firms require young professionals to take on heavy work loads while simultaneously facing significant risks of dismissal. We argue that the productivity of skilled partners in professional service firms (e.g. law, consulting, investment banking, and public accounting) is quite large relative to the productivity of their peers who are competent and experienced but not well-suited to the partner role. Therefore, these firms adopt personnel policies that facilitate the identification of new partners. In our model, both heavy work loads and up- or-out rules serve this purpose. Firms are able to identify more professionals who can function effectively as partners when they require new associates to perform more tasks. Further, when firms replace experienced associates with new less productive workers, they gain the opportunity to identify talented professionals who will have long careers as partners. Both of these personnel practices are costly. However, when the gains from increasing the number of talented partners exceed these costs, firms employ both practices in tandem. We present evidence on life-cycle patterns of hours and earnings among lawyers that support our claim that both heavy work loads and up-or-out rules are screening mechanisms.
Keywords: J44; J22; M51; 330; up-or-out; long hours; screening